Modular flow chamber for engineering bone marrow architecture and function. (November 2017) - Di Buduo, Christian A.; Soprano, Paolo M.; Tozzi, Lorenzo; Marconi, Stefania; Auricchio, Ferdinando; Kaplan, David L.; Balduini, Alessandra
Abstract: The bone marrow is a soft, spongy, gelatinous tissue found in the hollow cavities of flat and long bones that support hematopoiesis in order to maintain the physiologic turnover of all blood cells. Silk fibroin, derived from Bombyx mori silkworm cocoons, is a promising biomaterial for bone marrow engineering, because of its tunable architecture and mechanical properties, the capacity of incorporating labile compounds without loss of bioactivity and demonstrated ability to support blood cell formation. In this study, we developed a bone marrow scaffold consisting of a modular flow chamber made of polydimethylsiloxane, holding a silk sponge, prepared with salt leaching methods and functionalized with extracellular matrix components. The silk sponge was able to support efficient platelet formation when megakaryocytes were seeded in the system. Perfusion of the chamber allowed the recovery of functional platelets based on multiple activation tests. Further, inhibition of AKT signaling molecule, which has been shown to be crucial in regulating physiologic platelet formation, significantly reduced the number of collected platelets, suggesting the applicability of this tissue model for evaluation of the effects of bone marrow exposure to compounds that may affect platelet formation. In conclusion, we have bioengineered a novel modular system that, along with multi-porous silk sponges, can provide a useful technology for reproducing a simplified bone marrow scaffold for blood cell production ex vivo .